2016
DOI: 10.1016/j.addr.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) for delivery of bioactive macromolecules

Abstract: Therapeutic biomolecules often require frequent administration and supramolecular dosing to achieve therapeutic efficiencies and direct infusion into treatment or defect sites results in inadequate physiological response and at times severe side effects or mis-targeting. Delivery systems serve several purposes such as increased circulatory time, increased biomolecule half-life, and incorporation of new innovations can enable highly specific cell targeting and improved cell and nucleus permeability. Poly(lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 110 publications
0
21
0
Order By: Relevance
“…Therapeutic macromolecules (such as peptides and genes) are being actively developed as alternative to traditional chemotherapeutic drugs, which show widely observed serious side effects and poor patient compliance [133135]. Yu et al designed pH-responsive polymeric micelles that were mannosylated using “click” chemistry to achieve CD206 (mannose receptor)-targeted delivery siRNA to TAMs.…”
Section: Nanomedicines Targeting Dysfunctional Macrophage-associatmentioning
confidence: 99%
“…Therapeutic macromolecules (such as peptides and genes) are being actively developed as alternative to traditional chemotherapeutic drugs, which show widely observed serious side effects and poor patient compliance [133135]. Yu et al designed pH-responsive polymeric micelles that were mannosylated using “click” chemistry to achieve CD206 (mannose receptor)-targeted delivery siRNA to TAMs.…”
Section: Nanomedicines Targeting Dysfunctional Macrophage-associatmentioning
confidence: 99%
“…Because it is biocompatible and biodegradable, it has become a material of choice in biomedical applications [14][15][16]. This also includes the use of PLA for long-term controlled release of active ingredients [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that primary articular chondrocytes can be cultured in vitro on extrusion‐printed Acrylonitrile butadiene styrene and poly(lactic acid) (PLA) scaffolds with 700 µm pore size . PLA has a long history of tissue engineering, regenerative medicine, and drug delivery applications as an FDA approved biocompatible and degradable biopolymer . Scaffolds were developed in the shape of intervertebral discs.…”
Section: D Printing Proceduresmentioning
confidence: 99%